PENENTUAN KAWASAN ANDALAN MEBIDANGRO DI PROVINSI SUMATERA UTARA: ANALISIS BERDASARKAN PDRB PER KAPITA, PERTUMBUHAN EKONOMI DAN SPESIALISASI REGIONAL - elvis purba (Journal of Economic and Business, 2019)
This study aims to determine the accuracy of the determination of the Mebidangro region as a mainstay area based on three indicators, namely GDP per capita, economic growth, and regional specification. In connection with that the analytical tool used is Klaassen’s Typology Analysis, Regional Specialization Index, Binary Logistic Regression and Multinominal Logistic Regression. Based on Klaassen’s typology analysis, it turns out that only Medan City is in the category of “developed and fast growing regions”. Meanwhile, the City of Binjai, Deli Serdang Regency and Karo Regency are in the classification of “relatively lagging regions”. The results of the analysis of regional specialties show that the ability of the mainstay region as an area that has economic linkages with other regions is still weak. Based on the results of the analysis of binary logistic regression, the consideration of determining the mainstay area only refers to the GDP per capita. Based on the results of multinominal regression, it turns out that the determination of regional types based on the Klaassen typology is no better than the classification of the mainstay regions and non-mainstay regions. Based on the results of the analysis, I recommend it that all aspects of both per capita GRDP, economic growth and regional specialization be considered in determining the mainstay area. In addition, monitoring and evaluation of the functions of the mainstay area need to be monitored. Likewise, so that all regional leaders in Mebidangro’s mainstay to work together of Mebidangro urban areas.